2013
DOI: 10.1364/oe.21.023866
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of vector solitons in a highly birefringent cavity of ytterbium-doped fiber laser

Abstract: We report on the first experimental observation of dark-bright and dark-dark vector solitons in a highly birefringent cavity of all-normal-dispersion ytterbium-doped fiber laser. With the usage of different length of polarization maintaining fibers in the cavity, totally four types of vector solitons with different features were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…The propagation of vector solitons in circularly birefringent fibers was studied by the perturbation analytically and numerically and an effect leading to the polarization stabilization of circularly polarized vector solitons was found [15]. Four types of vector solitons with different characteristics were totally observed with the usage of different lengths of polarization maintaining fibers in the highly birefringent cavity of the all-normal-dispersion ytterbium-doped fiber laser [16]. A general formalism was developed for investigating the evolution of arbitrarily polarized short pulses in a birefringent fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The propagation of vector solitons in circularly birefringent fibers was studied by the perturbation analytically and numerically and an effect leading to the polarization stabilization of circularly polarized vector solitons was found [15]. Four types of vector solitons with different characteristics were totally observed with the usage of different lengths of polarization maintaining fibers in the highly birefringent cavity of the all-normal-dispersion ytterbium-doped fiber laser [16]. A general formalism was developed for investigating the evolution of arbitrarily polarized short pulses in a birefringent fiber.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the ultrashort pulse, which is also regarded as optical soliton, would exhibit fruitful polarization dynamics in the ultrafast fiber lasers as the result of the single mode fiber (SMF) supporting the two orthogonal polarization modes. So far, various vector soliton dynamics could be observed in passively mode locked fiber lasers [22]- [34], such as polarization-locked vector solitons (PLVSs) [22]- [24], [29], [30] and polarization-rotating vector solitons (PRVSs) [31]- [33]. Being different from the PLVS, the PRVS features that the pulse intensities along the two polarization components varied periodically with the cavity roundtrip time.…”
Section: Introductionmentioning
confidence: 99%
“…When operated in pulse states, most of the lasers produce bright pulses. However, it was shown that dark pulses or bright-dark pulses could be formed in fiber lasers [14][15][16][17]. Shao et al reported the formation of induced dark solitary pulses in a net anomalous dispersion cavity fiber laser, where the induced solitons were formed by the cross-phase modulation (XPM) between the two orthogonal polarization components of the fiber birefringence in the laser cavity [18].…”
Section: Introductionmentioning
confidence: 99%
“…When polarization maintaining fibers are used in the cavity, a fiber laser is considered to be highly birefringent. Different from a weakly birefringent cavity, the group velocity mismatch between the two orthogonal polarization components cannot be ignored in a highly birefringent fiber laser [16].…”
Section: Introductionmentioning
confidence: 99%